The Impact Of Smoking On Students' Knowledge In High School In Sragen, Central Java: THE IMPACT OF SMOKING - Rahmat Pannyiwi; Sulistyani Prabu Aji; Farid Setyo Nugroho; Nur Ani (STIKes Mandala Waluya Kendari, 2023)
Introduction: Smoking in everyday discourse is an act that has already got a bad stigma in society and also smoking in medical studies is an act that harms health for both active smokers and passive smokers. Methods: The research methodology is descriptive correlational research that is to determine the relationship between the impact of smoking on knowledge. This research was conducted in Sragen High School, Central Java. The number of samples in this study was 34, where these 35 students consisted of three classes, namely first grade: 12 students, second grade: 14 students, and third grade: 9 students, who met the inclusive and exclusive criteria. Results: The results showed that of the 35 students who were respondents, 24 students (68.6) showed the negative impact of smoking on health and 11 students (31.4%) showed the positive impact of smoking on health. Conclusion: this study prove d the truth of what we know, namely that smoking can cause death and various diseases at a greater rate that can be suffered by many smokers.